Development of a thin ceramic-graphene nanolaminate coating for corrosion protection of stainless steel. (April 2016) - Mondal, Jayanta; Marques, Andreia; Aarik, Lauri; Kozlova, Jekaterina; Simões, Alda; Sammelselg, Väino
Graphical abstract: Highlights: Developed anti-corrosion laminated graphene-oxide nanocoating for stainless steel. Graphene interlayer screens the alloy surface local fields. Atomic layer deposited oxide top coat improves well the coating passivity. The coating technology is industrial and environmentally friendly. The coating is biocompatible having titania outer surface. Abstract: A nanometric (thickness ≤200 nm) composite hybrid coating consisting of alternating laminate layers of aluminium and titanium oxides deposited by atomic layer deposition (ALD) onto a thin graphene layer of reduced graphene oxide (rGO) nanoplatelets applied on AISI 304 stainless steel, was developed and its electrochemical properties were studied. The rGO by itself has not revealed significant effects in terms of protection, whereas the laminate reinforced the passivity by decreasing the passive current. The best performance was obtained by the complete system, in which the rGO film acts as a primer for the anchoring of the ceramic layer, as a barrier for corrosive ions, and as a shield for local electrical fields if these are generated by starting local corrosion, thus, decreases the tendency to metastable pitting.